Top Ten Reasons to Use 100 mm Diameter Pipes in North America - John Gibson; Bryan Karney (Engineering Proceedings)
North American fire insurance and the American Water Works Association (AWWA) recommend that no pipes smaller than 150 mm in diameter are used in water distribution networks, mainly for reasons of fire protection. However, the 150 mm requirement reaches back more than one hundred years, cited by the AWWA at least as far back as 1916. In general, North American fire flow requirements are shown to be conservative compared to other places in the world. We show how pipe cost, water loss, water age, disinfection byproduct formation, contamination risks, and transients can all be improved with 100 mm diameter pipes. Perhaps most compelling is the fact that 100 mm pipes are used widely elsewhere. Perhaps it is time to consider permitting 100 mm pipes as the minimum recommended size for use in North America, especially in modern residential service.